Feeding Pattern and Nutritional Status of Under Two Years Slum Children - Akhtar, K; Haque, ME; Islam, MZ; Yusuf, MA; Sharif, AR; Ahsan, AI (Journal of Shaheed Suhrawardy Medical College, 2012)
Background: Feeding practices play a pivotal role in determining the optimal development of infants. Through this study the information helps to make planning to decrease malnutrition and way of proper feeding in reaching the target of MDG 4. Objective: The aim of the's present study was to assess feeding pattern and nutritional status of under two years children. Methodology: This cross sectional descriptive study was carried out in one slum of Dhaka City Corporation from January to June 2010. The study included 125 apparently healthy children and their mothers as respondents. Result: Among all the mothers 120 (96%) respondents fed their child colostrum; 54 (45.0%) respondents initiated breastfeeding within one hour of birth.105 (84%) respondents gave prelacteal feeding. only 20 (16%) respondents practiced exclusive breastfeeding for 6 months. It was revealed that 80 (64%) mothers fed their child complementary feeding at the age 6-7 months. Nutritional status of the children was in -<3SD including17.4% stunting, 19.1% wasting and 24.3% underweight. Conclusion: Traditional cultural barriers is still existed with poor practice of exclusive breast feeding while complementary feeding pattern had bizarre pattern. DOI: http://dx.doi.org/10.3329/jssmc.v4i1.11994 J Shaheed Suhrawardy Med Coll, 2012;4(1):3-6